This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: byrne (cmb3744) – HW 10 – rusin – (55565) 1 This printout should have 14 questions. Multiplechoice questions may continue on the next column or page – find all choices before answering. A short assignment to help you study the newest material while preparing for the test on TUESDAY 4/19. As before, this HW is not due until a little later than usual (Friday 4/22). What we discuss on Thursday 4/21 will be included on the next HW set (due 4/27). 001 10.0 points Find the slope in the xdirection at the point P (0 , 2 , f (0 , 2)) on the graph of f when f ( x, y ) = 2(2 x + y ) e − xy . 1. slope = 2 2. slope = 6 3. slope = 8 4. slope = 0 5. slope = 4 correct Explanation: The graph of f is a surface in 3space and the slope in the xdirection at the point P (0 , 2 , f (0 , 2)) on that surface is the value of the partial derivative f x at (0 , 2). Now f x = 4 e − xy 2(2 xy + y 2 ) e − xy . Consequently, at P (0 , 2 , f (0 , 2)) slope = 4 . 002 10.0 points Find u t when u = xe − 7 t sin θ . 1. u t = 7 xe − 7 t sin θ correct 2. u t = 7 e − 7 t sin θ 3. u t = e − 7 t sin θ 4. u t = xe − 7 t cos θ 5. u t = 7 xe − 7 t sin θ Explanation: Differentiating u = xe − 7 t sin θ with respect to t keeping x and θ fixed, we see that u t = 7 xe − 7 t sin θ . 003 10.0 points Determine f xy when f ( x, y ) = (2 x + 3 y )ln( xy ) . 1. f xy = 3 x 2 y x 2. f xy = 3 x 2 y xy 3. f xy = 2 x + 3 y y 4. f xy = 2 x + 3 y xy correct 5. f xy = 3 x + 2 y xy 6. f xy = 2 x 3 y xy Explanation: Since ln( xy ) = ln x + ln y , we see that f ( x, y ) = (2 x + 3 y )(ln x + ln y ) . byrne (cmb3744) – HW 10 – rusin – (55565) 2 Thus f x = 2(ln x + ln y ) + 2 x + 3 y x = 2(ln x + ln y ) + 2 + 3 y x . Consequently, after differentiating with re spect to y we see that f xy = 2 y + 3 x = 2 x + 3 y xy . 004 (part 1 of 4) 10.0 points A function f is defined by f ( x, y ) = ( x + 1)( y 9)( x + y 3) . (i) Determine f x for the function f . 1. f x ( x, y ) = ( y 9)(2 x + y 2) correct 2. f x ( x, y ) = ( y + 1)(2 x + y + 4) 3. f x ( x, y ) = ( x + 1)( x 2 y 2) 4. f x ( x, y ) = ( x 9)( x + 2 y 12) 5. f x ( x, y ) = ( y 9)(2 x y + 4) Explanation: Using the product rule to differentiate f ( x, y ) = ( x + 1)( y 9)( x + y 3) with respect to x we obtain f x = ( y 9)( x + y 3) + ( x + 1)( y 9) ....
View
Full
Document
This note was uploaded on 05/08/2011 for the course MATH 408D taught by Professor Chu during the Spring '09 term at University of Texas.
 Spring '09
 Chu

Click to edit the document details